The impact on innovation off-shoring on organizational adaptability - Elisabeth Baier; Christian Rammer; Torben Schuber (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We analyze the effects of captive off-shoring of innovation activities on the firms' ability to adapt their organizational processes and structures. Starting from complexity theory, we use three consecutive waves of the German part of the Community Innovation Survey to test our hypotheses. We find an inverted u-shape of innovation off-shoring on the effectiveness of organizational adaptability, implying an optimal threshold value of innovation off-shoring. This value is 11% for share of off-shored R&D, 15% for downstream innovation activities such as local market adaptation, and 34% for design activities. We also analyze several contingency variables. In particular we show that the costs of innovation off-shoring in terms of reduced organizational adaptability are exacerbated by a strong focus on R&D and a strong embeddedness in on-shore networks. Smaller firms find it easier to deal with the management complexity induced by geographical dispersion of innovation activities because of their greater flexibility.
urn:nbn:de:bsz:180-madoc-353018
Keywords: O32; M16; L23; L25; 330; Internationalization; Off-Shoring; Innovation; R&D; Organizational Adaptation; Organizational Adaptability